Traditional technologies of fuels production for air-jet engines - В., Бойченко С.; Черняк, Л. М.; Яковлєва, А. В. (Proceedings of National Aviation University (archive), 2013)
Available energy resources for various fuels, mainly for gas-turbine engines are presented in the given article. Traditional technologies for jet fuels production from nonrenewable raw materials, such as crude oil, coal, natural gas, oil-shales and others are analyzed in details. Cause and effect relationship between production and use of such fuels and their impact on natural environment is defined. The timeliness and necessity for development of alternative technologies of aviation biofuels production are determined in the given article.